Aesthetics of leadership: the example of Barack Obama - Ladkin, Donna (Henry Stewart Talks, 2017)
The case study examines the leadership style of Barack Obama, 44th president of the USA, and the way he used language, presentation, and stories to create a unique aesthetic for his leadership.